Practitioner review: A critical perspective on gene-environment interaction models--what impact should they have on clinical perceptions and practice? - Munafò, MR; Zammit, S; Flint, J (2014)
BACKGROUND: Psychiatric disorders run in families, and early twin, family and adoption studies confirmed that this was due in part to shared genetic inheritance. While candidate gene studies largely failed to reliably identify genetic variants associated with psychiatric disorders, genome-wide association studies are beginning to do so. However, the proportion of phenotypic variance explained remains well below what would be expected from previous heritability estimates. SCOPE: We review possible reasons for this 'missing heritability', and whether incorporating gene by environment interactions into our models will substantially improve our understanding of the aetiology of psychiatric disorders, and inform clinical perceptions and practice. FINDINGS: We discuss potential limitations of the gene by environment interaction approach. In particular, we discuss whether these are likely to be a major contributor to psychiatric disorders at the level of the specific interaction (as opposed to at an aggregate level). CONCLUSIONS: Gene by environment interaction studies offered initial promise that a far greater proportion of phenotypic variance could be explained by incorporating measures of environmental exposures into genetic studies. However, in our opinion, there are few (if any) clear examples of gene by environment interactions in psychiatry, and their scope for informing either our understanding of disease pathology or clinical practice remains limited at present.